The Effect of Threat Perception Towards Syrians on Xenophobia - Türk, Ahmet; Ervüz, Cezmi; Ervüz, Feyza (Fırat University, 2024)
This study aims to examine the impact of local people's perceptions of economic, security, environmental, and cultural threats posed by Syrian refugees on xenophobia in Turkey. The survey model was used in the study. A total of 466 people participated in the study, including 172 (36.9%) males and 294 (63.1%) females. The average age of the participants in the 18-70 age range is x?=27.23±9.15. The data for the study were collected using a Demographic Information Form, the Xenophobia Scale, and Perceptions of Syrians as a Threat Scale. Pearson correlation and multiple linear regression analyses were used in the data analysis. The findings indicate that the participants have a high level of xenophobia and threat perception. In the correlation analysis, a significant high level of correlation was found between the participants' levels of xenophobia and their perceptions of economic, security, environmental, and cultural threats. In the multiple linear regression analysis, the participants' perceptions of economic, security, and cultural threats towards Syrians were found to be significant predictors of xenophobia. The findings were discussed within the framework of the studies and interpreted within the context of the literature. Based on the results of the study, several recommendations were proposed.

Bu araştırma Türkiye’de yerel halkın Suriyeli göçmenlere yönelik ekonomik, güvenlik, çevresel ve kültürel tehdit algılarının yabancı düşmanlığına (zenofobi) etkisini incelemek amacıyla yapılmıştır. Araştırma kapsamında çalışmanın amacına uygun olarak tarama modeli kullanılmıştır. Araştırmaya 172’si (%36,9) erkek ve 294’ü (%63,1) kadın olmak üzere 466 kişi katılmıştır. 18-70 yaş aralığındaki katılımcıların yaş ortalaması x?=27,23±9,15’tir. Araştırmada veriler Kişisel Bilgi Formu, Yabancı Düşmanlığı (Zenofobi) Ölçeği ve Suriyelilere Yönelik Tehdit Algısı Ölçeği kullanılarak toplanmıştır. Normal dağılım gösteren verilerin analizinde Pearson korelasyon ve çoklu doğrusal regresyon analizleri kullanılmıştır. Bulgular, katılımcıların yüksek düzeyde yabancı düşmanlığına (zenofobi) ve tehdit algısına sahip olduğunu göstermektedir. Korelasyon analizinde katılımcıların yabancı düşamanlığı (zenofobi) düzeyleri ile ekonomik, güvenlik, çevresel ve kültürel tehdit algıları arasında yüksek düzeyde anlamlı olduğu tespit edilmiştir. Çoklu doğrusal regresyon analizinde katılımcıların Suriyelilere yönelik ekonomik, güvenlik ve kültürel tehdit algılarının yabancı düşmanlığının (zenofobi) anlamlı birer yordayısı olduğu saptanmıştır. Araştırma sonuçları literatürdeki çalışmalar çerçevesinde tartışılmış ve yorumlanmıştır. Araştırmanın bulgularından yola çıkarak birtakım öneriler sunulmuştur.
SURİYELİLERE YÖNELİK TEHDİT ALGISININ YABANCI DÜŞMANLIĞINA (ZENOFOBİ) ETKİSİ
Keywords: Migrant Cultural Studies; Göçmen Kültürü Çalışmaları